School feeding programs' role in forming eating habits - Ana Maria Cervato-Mancuso; Marcia Faria Westphal; Erica Lie Araki; Claudia Maria Bógus (Revista Paulista de Pediatria, 2013)
OBJECTIVE To identify teaching managers' perceptions regarding the relationship of school feeding and the promotion of healthy eating habits among students. METHODS A descriptive study with a qualitative approach was developed in the city of Guarulhos (Southeast Brazil). Key informants from municipal public schools were interviewed. Public schools were selected (n=13) and classified as to the level of social exclusion, size and economic activity of the region where the school was located. Pedagogic coordinators and school principals were individually interviewed with semi-structured questions. RESULTS From school principals and pedagogical coordinators' perceptions, three categories were identified: Food in the school context; School feeding program's role and the Concept of food and nutrition security, which indicate that they considered meals as part of school routine in order to attain physiological needs of energy and nutrients. Their answers also indicated that they did not consider school meals as a pedagogical action related to their specific responsibilities. CONCLUSIONS The relationship between the school feeding and the formation of eating habits is not a topic usually discussed between the different professionals involved with health and education. The implementation of health promoting policies will only be possible after a debate about how schools and their pedagogical team adopt the program guidelines and how the professionals decode these strategies in daily activities.